STRENGTHENING ISLAMIC RELIGIOUS EDUCATION LEARNING STRATEGIES BY PROFESSIONAL TEACHERS IN RESPONDING TO THE CHALLENGES OF GENERATION Z CHARACTERISTICS - Hartati, Herni (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2024)
This study aims to analyze the learning strategies for Islamic Religious Education (PAI) implemented by professional teachers in facing the challenges of Generation Z characteristics at SMP Negeri 5 Dumai. Generation Z, known for their tendency towards technology, critical thinking, and different learning styles, demands particular adaptations in teaching strategies. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. The study subjects were PAI teachers and Generation Z students at SMP Negeri 5 Dumai. The study results indicate that Generation Z's characteristics significantly influence the PAI learning. Students show greater interest in learning involving technology and interaction, while conventional lecture methods could be more attractive. Teachers face challenges in increasing student attention and adjusting learning methods to be more exciting and relevant. To overcome this, professional teachers develop innovative strategies, such as integrating technology into learning, using visual media and digital applications, and interactive discussion approaches. This study concludes that the success of PAI learning for Generation Z is greatly influenced by the teacher's ability to innovate and adapt to the unique characteristics of this generation. Thus, improving teacher competence in using technology and developing more exciting and contextual learning methods is necessary to increase the effectiveness of Islamic Religious Education learning in this digital era.